Enriched Environment-Induced Neuroprotection against Cerebral Ischemia-Reperfusion Injury Might Be Mediated via Enhancing Autophagy Flux and Mitophagy Flux - Zhang, Qi-Qi; Luo, Lu; Liu, Mei-Xi; Wang, Chuan-Jie; Wu, Yi; Yu, Ke-Wei (Mediators of Inflammation, 2022)
Background. Enriched environment (EE) can protect the brain against damages caused by an ischemic stroke; however, the underlying mechanism remains elusive. Autophagy and mitochondria quality control are instrumental in the pathogenesis of ischemic stroke. In this study, we investigated whether and how autophagy and mitochondria quality control contribute to the protective effect of EE in the acute phase of cerebral ischemia–reperfusion injury. Methods. We exposed transient middle cerebral artery occlusion (tMCAO) mice to EE or standard condition (SC) for 7 days and then studied them for neurological deficits, autophagy and inflammation-related proteins, and mitochondrial morphology and function. Results. Compared to tMCAO mice in the SC group, those in the EE group showed fewer neurological deficits, relatively downregulated inflammation, higher LC3 expression, higher mitochondrial Parkin levels, higher mitochondrial fission factor dynamin-related protein-1 (Drp1) levels, lower p62 expression, and lower autophagy inhibitor mTOR expression. Furthermore, we found that the EE group showed a higher number of mitophagosomes and normal mitochondria, fewer mitolysosomes, and relatively increased mitochondrial membrane potential. Conclusion. These results suggested that EE enhances autophagy flux by inhibiting mTOR and enhances mitophagy flux via recruiting Drp1 and Parkin to eliminate dysfunctional mitochondria, which in turn inhibits inflammation and alleviates neurological deficits. Limitations. The specific mechanisms through which EE promotes autophagy and mitophagy and the signaling pathways that link them with inflammation need further study.